Sodium nitroprusside enhanced CPR improves resuscitation rates after prolonged untreated cardiac arrest in two porcine models - Schultz, Jason C (2011)
OBJECTIVE: Sodium nitroprusside-enhanced CPR (SNPeCPR) consists of active compression decompression (ACD), impedance threshold device (ITD), abdominal binding (AB), and large intravenous doses of sodium nitroprusside (SNP). We hypothesize SNPeCPR will significantly increase carotid blood flow and return of spontaneous circulation compared to standard CPR after prolonged ventricular fibrillation (VF) and pulseless electrical activity (PEA) cardiac arrest. DESIGN: Prospective randomized animal study. SETTING: Hennepin County Medical Center Animal Laboratory. SUBJECTS: 40 Yorkshire female farm-bred pigs weighing 32 ± 2kg. INTERVENTIONS: In protocol A, 24 isoflurane anesthetized pigs underwent 15 minutes of untreated VF and were subsequently randomized to receive S-CPR (n=6), ACD CPR +ITD (n=6), or SNPeCPR (n=12) for up to 15 minutes. First defibrillation was attempted at minute 6 of CPR. In protocol B, a separate group of 16 pigs underwent 10 minutes of untreated VF followed by 3 minutes of chest compression only CPR followed by counter-shock induced PEA after which animals were randomized to S-CPR (n=8) or SNPeCPR (n=8). MEASUREMENTS AND MAIN RESULTS: The primary endpoint was carotid blood flow during CPR and return of spontaneous circulation (ROSC). Secondary endpoints included end-tidal CO(2) (ETCO(2)) as well as coronary (CPP) and cerebral perfusion pressure (CerPP). After prolonged untreated VF, SNPeCPR demonstrated superior rates of ROSC when compared to S-CPR and ACD CPR+ITD (12/12, 0/6, 0/6 respectively, p<0.01). In animals with PEA, SNPeCPR increased ROSC rates when compared to S-CPR. In both groups, carotid blood flow, CPP, CerPP, and ETCO(2) were increased with SNPeCPR. CONCLUSIONS: In pigs, SNPeCPR significantly increased ROSC rates as well as carotid blood flow and ETCO(2), when compared to S-CPR or ACD CPR+ITD.